Toxicity identification evaluation of landfill leachate using fish, prawn and seed plant. (September 2016) - Budi, Setia; Suliasih, B. Asih; Othman, Mohammad Shuhaimi; Heng, Lee Yook; Surif, Salmijah
Highlights: Very sensitive tropical species were successfully employed in TIE application. The test organisms can be handling properly without any special environment. All of the test organisms reveal mostly the same trend of TIE phase I result. Major toxicants of the leachate are basic, unstable, acidic and nonpolar organics. Abstract: The first phase of toxicity identification evaluation (TIE) method comprised of physic-chemical fractionation steps of pH adjustment, pH adjustment followed by filtration, aeration, extraction with solid phase C18 column (SPE), oxidant reduction with sodium thiosulphate and EDTA chelation was conducted to characterize the toxicants of a Malaysian landfill leachate. The battery of organisms test chosen were freshwater fish ( Rasbora sumatrana ), freshwater prawn ( Macrobrachium lanchesteri ) and tomato seed ( Lycoperson esculentum ). Toxicity reductions at each step were comparable for all test organisms. The major toxicants present in the leachate were found to be mostly basic in nature and precipitable under acidic conditions as well as containing non-polar organic compounds. A small reduction in toxicity was observed when leachate was treated with sodium thiosulphate in oxidant reduction test indicating the presence of oxidizers. The EDTA chelating step did not significantly reduce toxicity in the test organisms suggesting insignificant level of (toxic) metals.